3(1-7d)=33

Simple and best practice solution for 3(1-7d)=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1-7d)=33 equation:


Simplifying
3(1 + -7d) = 33
(1 * 3 + -7d * 3) = 33
(3 + -21d) = 33

Solving
3 + -21d = 33

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -21d = 33 + -3

Combine like terms: 3 + -3 = 0
0 + -21d = 33 + -3
-21d = 33 + -3

Combine like terms: 33 + -3 = 30
-21d = 30

Divide each side by '-21'.
d = -1.428571429

Simplifying
d = -1.428571429

See similar equations:

| 3(n-5)=14 | | 6(5+4r)=25 | | -4(9x-7)= | | -4aaa+2aaa-6aaa= | | (xxxxxxx)7= | | 2c-4+8=-15 | | x+(2x-21)=180 | | (x+16)+(5x-16)=90 | | -6(7y-4)=31-3y | | 3(4x-6)-4-(2x+5)= | | 4(-5+x)=15+3x | | 2x-13+4x=-1+6(x-2) | | 4(-5+x)=15+3 | | 25=-4(8a+2) | | -25=-3+8(x-4) | | 2n+5n=-28 | | 4x^4+33X^2+8=0 | | 21-5v=8(6v-9) | | 2(x-8)=6(x+2) | | 37=7+62 | | -9c-7-3=-29 | | 129-2x=25x+18 | | (6x-2)-(3x-1)=29 | | 3x+5=25-x | | x^3-10x^2+36x-36=0 | | 7(2-5x)=30 | | 50=16f+2 | | 24+9d=-3 | | -5a-6a=-15 | | ?x-2=0 | | -5a-6h=-15 | | 7m(60)= |

Equations solver categories